2019
DOI: 10.2174/1389201020666190417124711
|View full text |Cite
|
Sign up to set email alerts
|

Fenoldopam Mesylate: A Narrative Review of Its Use in Acute Kidney Injury

Abstract: Background: Fenoldopam mesylate is a selective agonist of DA-1 receptors. It is currently used for the in-hospital treatment of severe hypertension. DA-1 receptors have high density in renal parenchyma and for this reason, a possible reno-protective role of Fenoldopam mesylate was investigated. Method: We examined all studies regarding the role of Fenoldopam mesylate in Acute Kidney Injury (AKI); particularly, those involving post-surgical patients, intensive care unit patients and contrastinduced nephropath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 60 publications
1
14
0
Order By: Relevance
“…While the peripheral dopamine-1 receptor sites are located on blood vessels, renal tubules, and juxtaglomerular cells. At low doses, fenoldopam has a direct effect on the renal tubules which it has ability to produce natriuresis and diuresis ( Ricci and Ronco, 2006 ) and at the renal dose, fenoldopam has no any systemic effects ( Ricci and Ronco, 2006 ; Noce et al, 2019 ). In a small study, it was shown that fenoldopam exerted positive result by increasing blood flow in all renal compartments and the amelioration of renal blood flow produced in starting from a dose of 0.1–0.3 μg/kg/min with stable hemodynamic conditions of patients and preserved renal function ( Meco and Cirri, 2010 ).…”
Section: Fenoldopammentioning
confidence: 99%
See 1 more Smart Citation
“…While the peripheral dopamine-1 receptor sites are located on blood vessels, renal tubules, and juxtaglomerular cells. At low doses, fenoldopam has a direct effect on the renal tubules which it has ability to produce natriuresis and diuresis ( Ricci and Ronco, 2006 ) and at the renal dose, fenoldopam has no any systemic effects ( Ricci and Ronco, 2006 ; Noce et al, 2019 ). In a small study, it was shown that fenoldopam exerted positive result by increasing blood flow in all renal compartments and the amelioration of renal blood flow produced in starting from a dose of 0.1–0.3 μg/kg/min with stable hemodynamic conditions of patients and preserved renal function ( Meco and Cirri, 2010 ).…”
Section: Fenoldopammentioning
confidence: 99%
“…Administration of fenoldopam did not provide any benefit to patient which may experience deterioration in mean arterial pressure during cardiac surgery and in the presence of insufficient of renal function. Thereby the use of fenoldopam is appropriate for the prevention strategy of postoperative AKI ( Meco and Cirri, 2010 ; Noce et al, 2019 ).…”
Section: Fenoldopammentioning
confidence: 99%
“…From autopsy reports performed in the city of Wuhan, microscopic examination of the kidney revealed that AKI was induced by acute tubular necrosis, characterized by lumen dilation, vascular degeneration, and alteration of the tubular epithelium [ 121 , 125 ].…”
Section: Main Organ Damage Induced By Sars-cov-2mentioning
confidence: 99%
“…The blockade of either estrogen-induced (liganded) or unliganded activation of ERs provoked a strong compensatory upregulation on the unaffected domain, while the unbalanced ER activation resulted in modest or even adverse tumor responses and severe toxic symptoms [114]. In contrast, natural estrogens are capable of restoring DNA surveillance even in tumor cells leading to a self-directed death through a balanced liganded and unliganded transactivation of ERs, whereas they may not provoke genomic instability even in sky-high concentrations [115].…”
Section: Estrogen Is Protective Against Cancermentioning
confidence: 99%
“…This study did not examine the impact induced by the body surface area on CV protection. Therefore, calcium antagonists emerge as a pharmaceutical alternative in the treatment of obesity-related hypertension with potential benefits [113], even if more clinical randomized trials are required to fully understand their beneficial effects [114,115].…”
Section: Other Antihypertensive Drugsmentioning
confidence: 99%